A system based on deep convolutional neural network improves the detection of early gastric cancer - Feng, Jie; Yu, Shang rui; Zhang, Yao ping; Qu, Lina; Wei, Lina; Wang, Peng fei; Zhu, Li juan; Bao, Yanfeng; Lei, Xiao gang; Gao, Liang liang; Feng, Yan hu; Yu, Yi; et al. (Frontiers in Oncology, 2022)
Abstract Background: Early gastric cancer (EGC)has a high survival rate, but it is difficult to diagnosis. Recently, artificial intelligence (AI)based on deep convolutional neural network (DCNN) has made significant progress in the field of gastroenterology. The purpose of this study was to establish a DCNN assist system to improve the detection of EGC.